Somatic embryogenesis induction of Syzygium cumini - Mahrous H Mahrous; Amr El-Hawiet; Amany E Ragab; Hala M Hammoda; Fathy K EL-Fiky (Open Journal of Plant Science - Peertechz Publications, 2023)
Somatic embryogenesis serves as an effective alternative system for in vitro cultivation of endangered plants (Syzygium cumini), as it allows for the propagation of plants under a controlled environment. So produce hundreds of embryos that can be used as artificial seeds. Somatic embryos of Syzygium cumini, family Myrtaceae, were induced from the calli of a sterile leaf explant in Murashige and Skoog's medium with 6 ppm 2,4-D. After the transfer of the developed calli into liquid media supplemented with the same concentration of growth regulator, all three embryonic stages (globular, heart and torpedo) were observed after 6 weeks. Liquid media with growth regulators appeared to enhance the development to torpedo-stage embryos, especially at six weeks of age cultures. 12 weeks after the transfer of the callus into liquid media, flasks containing predominantly one microscopic stage were pooled and plated on fresh solid media lacking a growth regulator, where the embryogenic calli germinated showing shoots and aerial parts. Embryogenesis production protocol is considered a good tool to save plants from extinction, especially in Syzygium cumini which is a very important anti-diabetic drug.